Towards the Mungbean ‘Peptidome’: Assessing the Bioactivity of Low Molecular Weight Peptides Isolated from Germinating Seeds - Agrawal4, J. Shibato3,5, and P.K. Sircar6, A. Sarkar1,6*, R. Rakwal2,3,4#, G.K. (Journal of Phytology, 2011)
Numerous studies have established that peptides function as signaling molecules, and play significant role in cell-to-cell communication in almost all living organisms. In plants, the impact and importance of ‘peptide signaling’ in regulation of growth and development has triggered challenges over the classical definition and function of ‘traditional plant hormones’. In the present study, we isolated the complete ‘peptidome’, consisting of low molecular weight peptides in the range of 3 kDa to 0.5 kDa, of germinating mungbean [Vigna radiata (L) Wilckzek. cultivar Sonali B1] at different hours of germination. A comparative profiling of the peptidome was done through thin layer chromatography, followed by an evaluation of their bioactivity in vitro. Majority of peptides were found to be abundantly present at 24, 48 and 72 h of germination; however, showed a significant decrease at 120 and 144 h of germination. Bioactivity analysis revealed that peptides isolated at 24, 48 and 72 h, but not 120 and 144 h of germination showed positive and inductive control over α-amylase activity and cell division in vitro. Our results suggest towards the conditional synthesis of specific types of low molecular weight peptides during active germination in mungbean plants.